Management of Bronchiolitis with mucolytic agent (3% NaCl) in children in a hospital in Dhaka City without antibiotic (The Journal of Ad-din Women's Medical College, 2023)
Background: Bronchiolitis is mostly a viral disease of lower respiratory tract in infants and young children. Variation in the management has been documented. Treatment with 3 % hypertonic saline has a significantly shorter mean length of hospital stay and improved clinical severity score. Antibiotic has little role in the management of bronchiolitis though it is invariably prescribed. However, management of bronchiolitis is yet not optimized according to recommendation.Objective: To evaluate the outcome of bronchiolitis with 3% Nacl nebulization without antibiotic.Methodology: This observational study was conducted in Ad-din Medical College Hospital at the department of pediatrics during October, 2018 to January, 2019. Among 92 cases of clinically diagnosed bronchiolitis 30 were excluded due to prior antibiotic therapy and rest 62 cases were enrolled based on inclusion criterions (age below 2 years, 1st or 2nd episode of wheeze, runny nose, cough, respiratory distress, wheeze/ ronchi, hyperinflation / increased translucency on CXR). Consent of the parents was taken. A structured questionnaire was filled up. Detailed history was taken and full physical examination was done. CBE with PBF, CRP& CXR were done immediately after admission. All children were managed with 6 hourly 3% Nacl nebulization in addition to supportive measures whenever indicated like IV 5% dextrose in 0.225% saline, O2 inhalation, paracitamol for fever and were followed 8 hourly. Patients were discharged after returning of social smile, absence of feeding diflculty, fast breathing and free of O2 therapy. However, thirty cases were taken out of the study for increased severity or persistence of symptoms. So finally data were analysed in 32 cases using SPSS 22.Results: Mean age of presentation was 5 months, 75% in male children. Cough and respiratory distress were present in 100 % cases, wheezing (71%), runny nose and absence of social smile in 56% cases, fever (53%), feeding diflculty (50%), vomiting (28%) sleeping diflculty (25%), subcostal recession (100%) fast breathing (68%), mouth breathing (45%), nasal flaring (40%), intercostal recession (9%), low grade fever (37%), SPO2 < 90% ( 71%), vesicular breath sound with prolong expiration ( 75%), bilateral ronchi (100%), bilateral crepitation (15%). Total leulocyte count was normal (